Instructions for formatting JIOS articles : a microsoft word template - Lovrenčić, Alen (Array, 2009)
Abstract: This document describes the required formatting of JIOS papers, including margins, fonts, citation styles, and figure placement. The template provided here is made to coincide with jios.sty LaTeX style. While the format requirements are only compulsory for final submissions, we strongly encourage authors to adopt this template, as well as its recommendations throughout the submission process. Keywords: format, Microsoft word template, JIOS.